2010
DOI: 10.3844/ajassp.2010.1093.1099
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Cluster Bed-Form Formation Over Uniform Sediment

Abstract: Problem statement: Cluster microforms are a type of small scale bed-form found in the surface layer of some gravel bed rivers. These bed-forms are comprised of discrete, organized groupings of particles that sit above the average elevation of the surrounding bed. As part of the structural organization of the bed, clusters are believed to impact the local dynamics of the fluvial system through the feedback process involving the flow field, entrainable sediment and stable bed morphology. Approach: In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Past approaches to the quantification of bed form variability have used and applied spectral analysis [ Hino , ; Jain and Kennedy , , ; Annambhotla et al , ; Levey et al , ; Kheiashy et al , ], smoothing techniques such as a moving average [ Brinke et al , ; Julien et al , ; Wilbers and Brinke , ; Hoekstra et al , ; Frings and Kleinhans , ; van der Mark et al , ], signal roughness techniques [ Singh et al , ], fractals [ Wildhaber et al , ], and logistic regression [ Karbasi et al , ]. However, past research concerning the analysis of time series exhibiting multiscale time variability (similar to the multiscale spatial variability of bed form features) using moving average techniques, as well as Fourier series analysis, has generally shown that these techniques are insufficient as a tool to extract the long‐term variation from signals that contain a long‐term trend with a superimposed fine oscillation (i.e., the short term variation) [ Takezawa , ].…”
Section: Introductionmentioning
confidence: 99%
“…Past approaches to the quantification of bed form variability have used and applied spectral analysis [ Hino , ; Jain and Kennedy , , ; Annambhotla et al , ; Levey et al , ; Kheiashy et al , ], smoothing techniques such as a moving average [ Brinke et al , ; Julien et al , ; Wilbers and Brinke , ; Hoekstra et al , ; Frings and Kleinhans , ; van der Mark et al , ], signal roughness techniques [ Singh et al , ], fractals [ Wildhaber et al , ], and logistic regression [ Karbasi et al , ]. However, past research concerning the analysis of time series exhibiting multiscale time variability (similar to the multiscale spatial variability of bed form features) using moving average techniques, as well as Fourier series analysis, has generally shown that these techniques are insufficient as a tool to extract the long‐term variation from signals that contain a long‐term trend with a superimposed fine oscillation (i.e., the short term variation) [ Takezawa , ].…”
Section: Introductionmentioning
confidence: 99%